2019
DOI: 10.4103/jnrp.jnrp_348_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Essential Tremor in South India: A Hospital-Based Cohort Study

Abstract: Introduction: Essential tremor (ET) is the most common adult movement disorder. Classic ET is characterized by action tremor of hands (95% cases), and tremor involving other regions is less common. Recent studies have revealed a few patients exhibiting nontremor features that include cognitive disorders, tandem gait abnormality, mood fluctuations, olfactory abnormality, hearing impairment, and sleep disorders. Very few studies on ET have so far been conducted in India, and the present study is a pioneering att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Importantly, the prevalence of RT in ET has reported to be dependent on the recruitment setting, being the lowest in population-based setting and highest in a brain bank study (Louis et al 2015 ). In many (Rajalingam et al 2018 ; Bellows and Jankovic 2021 ; Campbell et al 2022 ; Prasad and Pal 2019 ; Peng et al 2022 ; Gilmour et al 2021 ; Steffen et al 2020 ), but not all studies (Pandey and Bhattad 2021 ; Manorenj et al 2019 ), ET + RT was among the commonest ET-plus subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the prevalence of RT in ET has reported to be dependent on the recruitment setting, being the lowest in population-based setting and highest in a brain bank study (Louis et al 2015 ). In many (Rajalingam et al 2018 ; Bellows and Jankovic 2021 ; Campbell et al 2022 ; Prasad and Pal 2019 ; Peng et al 2022 ; Gilmour et al 2021 ; Steffen et al 2020 ), but not all studies (Pandey and Bhattad 2021 ; Manorenj et al 2019 ), ET + RT was among the commonest ET-plus subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Such additional signs have been noted to be present so frequently that the majority of ET patients in many studies have been classified as ET plus rather than ET [51][52][53][54]. Prevalence of rest tremor in patients with ET varies in different reports: 1.9% [55], 13.3% [56], 14% [57], 18.8% [58], 43.3% [53], and 46.4% [55]. Jaw tremor, classically present in PD, has been reported in 7.5% to 26.8% of patients with ET [59,60].…”
Section: Essential Tremormentioning
confidence: 99%
“…• Rest tremor can be present in 13.3 [56] to 46.4% of ET patients [55] • Parkinsonism can be seen in 20% of ET patients [63] • Kinematic studies have shown slower movements in ET without clear decrement [64] • ET-PD patients more likely to have asymmetric onset than ET patients [75] ET-Dystonia…”
Section: Pure Etmentioning
confidence: 99%